Differential Calculi on Super-Hopf Algebra F(Rq(1|2)) - Celik, Sultan Abaci (SPRINGER BASEL AG, 2018)
It is constructed two-parameter left-covariant differential calculi on the function algebra on Rq(1 vertical bar 2) with respect to super-Hopf algebra O(GLp, q(1 vertical bar 2)). It is shown that, one of the differential calculi is bicovariant with respect to the super-Hopf algebra F(Rq(1 vertical bar 2)). It is noted that there is another two-parameter differential calculus which is bicovariant with respect to F(Rq(1 vertical bar 2)).
Keywords: Quantum superspaces; Super-Hopf algebra; Differential calculus; Quantum supergroup; QUANTUM; DEFORMATION; Mathematics; Physics